Electric pulse treatment method for quickly prolonging fatigue life of notched pure titanium component
Through electrical pulse processing technology, high-density current is applied to the pure titanium component with notch, which promotes microstructure phase transformation and grain refinement, solving the problem that titanium components are prone to cracks during fatigue, and significantly extends their fatigue life.
Patent Information
- Application Number
- CN202411915154.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
Titanium components exhibit severe notch sensitivity under cyclic loads, resulting in their susceptibility to cracks and early damage during fatigue, limiting their reliability and life.
Using electrical pulse processing technology, high-density DC pulse current is applied to both ends of the notched pure titanium component in a very short time, so that the temperature at the notch tip is increased to 1000°C, promoting phase transformation and nucleation of microstructure, refining grains, and inducing high-density dislocations and residual compressive stresses inside.
It effectively inhibits the initiation and expansion of cracks, realizes complete repair of microcracks caused by fatigue, and significantly improves the overall durability and fatigue life of the notched pure titanium components, with a service life extension rate of more than 20 times.
Smart Images

Figure CN119843193A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal fatigue crack repair and fatigue life extension, and in particular to an electric pulse processing method for rapidly improving the fatigue life of a notched pure titanium component. Background Art
[0002] Titanium components have excellent mechanical properties such as high specific strength, excellent corrosion resistance and good biocompatibility, and are highly valued in various industries. Despite these advantages, titanium components show severe notch sensitivity when subjected to cyclic loading, which limits their reliability and life. Therefore, it is necessary to develop effective technologies to improve the resistance of notched titanium components to fatigue crack initiation and propagation, thereby extending their fatigue life.
[0003] At present, the technology used to improve the fatigue crack initiation and propagation resistance of notched titanium components is mainly laser shock strengthening (Reference 1: Weiwei Deng, Changyu Wang, Haifei Lu, Xiankai Meng, Zhao Wang, Jiming Lv, Kaiyu Luo, Jinzhong Lu. Int. J. Mach. Tool. Manu. 191 (2023) 104061), which is characterized by high cost, non-contact, and difficulty in processing complex structural parts. At present, laser shock strengthening technology has been deeply studied and widely used, but there are still many problems to be solved in this technology, including that this technology can only act on the surface, and the depth of residual compressive stress is limited; it is difficult to repair fatigue damage in complex structural parts, etc., and it cannot completely solve the problem of fatigue failure of notched specimens.
[0004] In summary, developing a technology that can deeply strengthen, accurately locate and repair damage to improve the ability of pure titanium components to resist fatigue initiation and expansion is of great significance for industrial production and manufacturing. Summary of the invention
[0005] According to the technical problems mentioned in the above background technology, an electric pulse treatment method for rapidly improving the fatigue life of notched pure titanium components is provided. The present invention adopts electric pulse treatment technology to effectively promote the phase transformation and nucleation process of the microstructure at the notch of the pure titanium component in a very short time, significantly refine the grains in the notch area, and induce high-density dislocations and residual compressive stresses inside the grains, thereby effectively inhibiting the initiation and expansion of cracks, and achieving complete repair of microcracks caused by fatigue, thereby comprehensively improving the overall durability and fatigue life of notched pure titanium components.
[0006] The technical means adopted by the present invention are as follows:
[0007] The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component comprises the following steps:
[0008] Step 1: Clamp the notched pure titanium sample on the electric pulse processing equipment;
[0009] Step 2: applying a high-density direct current pulse current to both ends of the notched pure titanium sample to increase the peak temperature of the notch tip to 1000° C.;
[0010] Step 3: Stop applying the DC pulse current to the notched pure titanium sample, remove the notched pure titanium sample, and cool the notched pure titanium sample to room temperature.
[0011] Furthermore, the notch shape of the notched pure titanium sample is V-shaped and U-shaped.
[0012] Furthermore, the heating rate of the notched pure titanium sample is greater than or equal to 1500° C. / s, and the notch temperature gradient of the notch pure titanium sample is not less than 200° C. / mm.
[0013] Furthermore, the intensity of the DC pulse current is 900-1100A, and the density is 80-120A / mm 2 .
[0014] Furthermore, the notch of the notched pure titanium sample undergoes a transformation from HCP (α) to BCC (β) phase during the heating process under the microstructure, and then transforms into α phase when the current is removed and the sample is naturally cooled to room temperature.
[0015] Furthermore, the total pulse time of applying the DC pulse current in step 2 and step 3 is 0.4 to 0.5 s.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] 1. In the present invention, current is passed through both ends of the notched titanium component, and the current flows around the notch and is concentrated at the tip of the notch, thereby achieving accurate positioning and automatic repair of fatigue damage, and is therefore more suitable for complex structural parts.
[0018] 2. In the present invention, electric current is passed through both ends of the notched titanium component. When the current flows around the notch, it is enriched, thereby generating more Joule heat and producing an extremely high temperature gradient, ensuring that the phase transition temperature is reached near the notch while no microstructural changes occur in other locations, thereby achieving local strengthening while ensuring the ductility of the matrix.
[0019] 3. The present invention passes current through both ends of the notched titanium component. The current duration is very short, and the current flows directly through the notch and converts the electrical energy into Joule heat, thereby reducing energy dissipation, improving energy utilization, and saving energy and protecting the environment.
[0020] 4. In the present invention, the current flows through the inside of the notched titanium component to ensure the depth of residual compressive stress, which can inhibit the initiation and expansion of cracks in the deep layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 It is a schematic diagram of the device of the present invention.
[0023] Figure 2 Schematic diagram of the electric pulse treatment parameters of the present invention, wherein (a) represents the change of current intensity over time; (b) represents the change of temperature over time.
[0024] Figure 3 The diagram is a distribution diagram of the electrothermal simulation results of the current and temperature of the present invention, wherein (a) represents the temperature distribution of the whole component; (b) represents the current density distribution; and (c) represents the temperature distribution of the notch area.
[0025] Figure 4 This is a schematic diagram of the experimental process of using electric pulses to repair fatigue damage cracks and extend life in the present invention.
[0026] Figure 5 It is the micromorphology at the notch of the sample of the present invention; wherein, (a) represents the micromorphology at the notch of the pure titanium component after 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1 and frequency 10Hz; (b) represents the micromorphology at the notch of the titanium component after 33344 fatigue cycles, electric pulse treatment and then cyclic loading for 1 million times.
[0027] Figure 6 The phase diagram, XRD diagram and pole diagram of the sample of the present invention are shown in Figures 1 and 2. (ac) are phase diagrams; (d) are XRD diagrams; and (e) are pole diagrams.
[0028] Figure 7 This is the grain size analysis of the sample of the present invention; wherein (a) represents the grain size of the base material; (b) represents the grain size at the notch of the titanium component after 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1 and frequency 10Hz; (c) represents the grain size at the notch of the titanium component after 33344 fatigue cycles and then subjected to electric pulse treatment.
[0029] Figure 8It is the average orientation difference of the Kernel crystal of the present invention; wherein (a) represents the average orientation difference of the Kernel crystal of the base material; (b) represents the average orientation difference of the Kernel crystal at the notch of the titanium component after 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1 and frequency 10Hz; (c) represents the average orientation difference of the Kernel crystal at the notch of the titanium component after 33344 fatigue cycles and then subjected to electric pulse treatment.
[0030] Fig. 9 It is the residual compressive stress in the notch tip area before and after the electric pulse of the present invention.
[0031] In the figure: 1. Notched titanium component; 2. Copper electrode; 3. Slide rail; 4. Insulating base; 5. DC power supply; 6. Thermal imaging camera; 7. Control unit. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0033] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0034] like Figure 1 As shown, the electric pulse processing device used in the present invention. The device includes a copper electrode 2, a slide rail 3 and an insulating base 4. The copper electrode 2 is mounted on the insulating base 4, and the slide rail 3 is fixed on the insulating base 4; the two ends of the notched titanium component 1 are clamped on the copper electrode 2. The control program 7 controls the DC power supply 5 to output current to the copper electrode 2, which acts on the notched titanium component 1. The control program 7 and the thermal imaging camera 6 are used to constantly observe the power-on time and the temperature near the notch of the notched titanium component. When the time is reached, the power is stopped, the notched titanium component is removed, and cooled to room temperature.
[0035] In the present application, an electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component comprises the following steps:
[0036] Step 1: Clamp the notched pure titanium sample on the electric pulse processing equipment; the notch shape of the notched pure titanium sample is V-shaped and U-shaped. The heating rate of the notched pure titanium sample is greater than or equal to 1500℃ / s, and the temperature gradient of the notch of the notched pure titanium sample is not less than 200℃ / mm. Under the microstructure, the notch of the notched pure titanium sample undergoes a transformation from HCP (α) phase to BCC (β) phase during the heating process, and then transforms into α phase when the current is removed and naturally cooled to room temperature.
[0037] Step 2: Apply high-density DC pulse current to both ends of the notched pure titanium sample to raise the peak temperature of the notch tip to 1000°C; the intensity of the DC pulse current is 900-1100A, and the density is 80-120A / mm 2 .
[0038] Step 3: Stop applying the DC pulse current to the notched pure titanium sample, remove the notched pure titanium sample, and cool the notched pure titanium sample to room temperature.
[0039] In the present application, preferably, the total pulse time of applying the DC pulse current in step 2 and step 3 is 0.4 to 0.5 s.
[0040] In the present application, the microstructure nucleation near the notch of the titanium component during the electric pulse treatment method of the present application is an average grain size ( Figure 7 The AGS) was reduced from 80-120 μm to 50-60 μm.
[0041] After electric pulse treatment, the residual compressive stress near the notch of the titanium component increased from 30-50MPa to 200-250MPa.
[0042] After electric pulse treatment, the length of microcracks near the notch of the titanium component was reduced from 100 to 500 μm to completely repaired.
[0043] After electric pulse treatment, the fatigue life of notched pure titanium components was significantly extended from 55,000 times to more than 1 million times.
[0044] Example 1
[0045] In this embodiment, the electric pulse processing method for rapidly extending the fatigue life of a notched titanium component comprises the following steps:
[0046] (1) Clamp the pure titanium component with a V-notch on the electric pulse processing equipment, such as Figure 1 As shown;
[0047] (2) Apply 900A / 0.4s (900A≈88A / mm) to both ends of the sample. 2 ) current increases the notch temperature. The heating rate is 2682.5℃ / s, and the expected temperature is 1073℃. The current intensity changes with time as shown in Figure 2 (a) shows the temperature variation curve over time. Figure 2 (b) as shown.
[0048] (3) After the time is up, stop applying current and remove the sample, and cool it to room temperature.
[0049] Figure 3 The electrothermal simulation results of current and temperature. Figure 3 (a) shows that the temperature is concentrated in the notch; Figure 3 (b) shows that the current flows from top to bottom through the gap, where the current flows around and concentrates, resulting in uneven current distribution; Figure 3 (c) shows that the highest temperature at the notch is 1178°C, and the temperature decreases step by step as it moves away from the notch. The temperature gradient at the notch reaches about 200°C / mm.
[0050] Table 1 Fatigue test parameters and fatigue life before and after electric pulse treatment
[0051]
[0052] Table 1 shows the fatigue test parameters and fatigue life before and after electric pulse treatment. Among them, the fatigue test parameters are stress 120MPa, stress ratio 0.1, frequency 10Hz; the fatigue life before electric pulse treatment is about 55,000 times, and the average fatigue life is 55,573 times; after 33,344 fatigue cycles and then electric pulse treatment, the average fatigue life of the notched pure titanium component exceeds 1 million times and no specimen fracture occurs.
[0053] Figure 4 Schematic diagram of the experimental process of repairing fatigue damage cracks and extending life by electric pulse. First, the notched pure titanium component is placed in a fatigue testing machine and cyclically loaded for 33,344 cycles at 120 MPa and a stress ratio of 0.1; then it is placed in an electric pulse treatment device for electric pulse treatment; finally, it is placed in a fatigue testing machine again and subjected to 1 million fatigue cycles under the same experimental conditions. If the sample is not damaged, it is removed.
[0054] Figure 5 This is the microstructure of the notch during the electric pulse treatment. After 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1, and frequency 10Hz, microcracks can be observed at the notch of the pure titanium component, such as Figure 5 (a) As shown. After the electric pulse treatment, the microcracks disappeared, and no fatigue cracks were generated after 1 million cycles of loading. Figure 5 (b).
[0055] Figure 6 Phase diagram, XRD diagram and pole figure of the sample. Figure 6 The phase diagram of (ac) shows that the notched pure titanium component at room temperature only has α phase before and after the electric pulse treatment, and the grains around the notch are refined after the electric pulse treatment. However, during the electric pulse process, the temperature around the notch exceeds the phase transition temperature of 882℃. Therefore, before and after the electric pulse treatment, the microstructure around the notch undergoes a process of heating up to transform HCP (α) to BCC (β), cooling to room temperature and then transforming to α phase, which changes the nucleation and growth mode of the α phase variant during the cooling process, resulting in grain refinement. Figure 6 The XRD phase diagram (d) shows that after the electric pulse treatment, the relative diffraction intensity of the (1011) plane remains unchanged, while the relative diffraction intensity of the (1010) plane is significantly enhanced. At the same time, a new lattice orientation appears in the (1120) plane with a higher relative diffraction intensity, indicating that the lattice has slipped and rotated. Figure 6 The pole figure of (e) shows that the texture is weakened, with the maximum strength decreasing from 22.5 of the parent material to 10.7 after the electric pulse treatment. This texture weakening is mainly due to the current-induced phase transformation, which leads to grain refinement and changes the grain orientation at the root of the notch. This weakened texture can significantly improve the toughness of the pure titanium notch, and still has a strong resistance to crack initiation after enduring more fatigue load cycles.
[0056] Figure 7 The microstructure of the sample is shown in Figure 2. After 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1, and frequency 10Hz, Figure 7 (a) Evolution to Figure 7 (b), the average grain size grows from 83.3μm to 112.1μm. After the electric pulse treatment, the grain morphology changes from Figure 7 (b) Evolved into Figure 7 (c), the average grain size decreases from 112.1 μm to 58.9 μm.
[0057] Figure 8 is the average orientation difference of the Kernel crystal of the sample. After 33344 fatigue cycles under the conditions of 120MPa stress, stress ratio 0.1, and frequency 10Hz, Figure 8 (a) Evolution to Figure 8 (b) The average orientation difference of the overall Kernel crystal did not increase significantly, but the orientation difference in the area around the microcrack generated at the notch tip increased significantly. After the electric pulse treatment, the average orientation difference of the Kernel crystal increased from Figure 8 (b) Evolved into Figure 8 (c), the misorientation is greatly enhanced at the notch tip, suggesting that extremely high residual stress is generated there.
[0058] Fig. 9 is the residual compressive stress of the sample. After the electric pulse treatment, the residual stress at the notch tip increased from 40.8MPa to 239.9MPa.
[0059] In summary, the present invention can effectively promote the phase transformation and nucleation process of the microstructure in a very short time, while activating the slip and rotation of the lattice, significantly refining the grains in the notch area, and inducing high-density dislocations and residual compressive stresses inside the grains, thereby effectively inhibiting the initiation and expansion of cracks, and achieving complete repair of fatigue-induced microcracks, thereby comprehensively improving the overall durability and fatigue life of notched titanium components, and the life extension rate is increased by more than 20 times. The key to the electric pulse treatment method is to regulate the temperature at the notch, the size and time of the DC current, etc. The present invention introduces deeper residual compressive stresses, which can be applied to complex structural parts and is more widely used than laser shock strengthening. In addition, the input current of the present invention lasts for a very short time, and the current flows directly through the notch and converts electrical energy into Joule heat, which reduces energy dissipation, improves energy utilization, saves energy and protects the environment, and is expected to be important in the field of crack repair.
[0060] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0061] In the above embodiments of the present invention, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0062] In the several embodiments provided in this application, it should be understood that the disclosed technical content can be implemented in other ways. Among them, the device embodiments described above are only schematic. For example, the division of the units can be a logical function division. There may be other division methods in actual implementation. For example, multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be through some interfaces, indirect coupling or communication connection of units or modules, which can be electrical or other forms.
[0063] The units described as separate components may or may not be physically separated, and the components shown as units may or may not be physical units, that is, they may be located in one place or distributed on multiple units. Some or all of the units may be selected according to actual needs to achieve the purpose of the present embodiment.
[0064] In addition, each functional unit in each embodiment of the present invention may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit. The above-mentioned integrated unit may be implemented in the form of hardware or in the form of software functional units.
[0065] If the integrated unit is implemented in the form of a software functional unit and sold or used as an independent product, it can be stored in a computer-readable storage medium. Based on this understanding, the technical solution of the present invention, in essence, or the part that contributes to the prior art, or all or part of the technical solution can be embodied in the form of a software product, and the computer software product is stored in a storage medium, including a number of instructions for a computer device (which can be a personal computer, a server or a network device, etc.) to perform all or part of the steps of the method described in each embodiment of the present invention. The aforementioned storage medium includes: U disk, read-only memory (ROM, Read-Only Memory), random access memory (RAM, Random Access Memory), mobile hard disk, magnetic disk or optical disk and other media that can store program codes.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electric pulse treatment method for rapidly improving the fatigue life of notched pure titanium components, characterized in that: The following steps are involved: Step 1: Clamp the notched pure titanium sample on the electric pulse processing equipment; Step 2: applying a high-density direct current pulse current to both ends of the notched pure titanium sample to increase the peak temperature of the notch tip to 1000° C.; Step 3: Stop applying the DC pulse current to the notched pure titanium sample, remove the notched pure titanium sample, and cool the notched pure titanium sample to room temperature.
2. The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component according to claim 1 is characterized in that: The notch shapes of the notched pure titanium sample are V-shaped and U-shaped.
3. The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component according to claim 1 is characterized in that: The heating rate of the notched pure titanium sample is greater than or equal to 1500°C / s, and the notch temperature gradient of the notch pure titanium sample is not less than 200°C / mm.
4. The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component according to claim 1 is characterized in that: The intensity of the DC pulse current is 900-1100A, and the density is 80-120A / mm 2 .
5. The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component according to claim 1, characterized in that: The notch of the notched pure titanium sample undergoes a transformation from HCP (α) to BCC (β) phase in the microstructure during the heating process, and then transforms into α phase when the current is removed and the sample is naturally cooled to room temperature.
6. The electric pulse treatment method for rapidly improving the fatigue life of a notched pure titanium component according to claim 1 is characterized in that: The total pulse time of applying the DC pulse current in step 2 and step 3 is 0.4 to 0.5 s.